Pelatihan Penggunaan Sosial Media untuk Mengembangkan Akses Pasar bagi UMKM Kabupaten Serang - Sindy Yulia Putri; Wiwiek Rukmi Dwi Astuti; Nurmasari Situmeang (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2020)
With advances in digital technology, MSMEs have great opportunities to take part in it. Various SMEs in Serang Regency are still experiencing problems in promoting their merchandise. This community service program (PKM) aims to transfer knowledge about the use of social media to develop market access for MSMEs in Serang Regency. Indonesia is still facing the Covid-19 pandemic. Therefore, the socialization and training methods are carried out through online webinars with interactive discussion. This discussion is useful for finding solutions to problems faced by MSME business actors in operating social media to increase income. The result of this PKM is that the participants understand the webinar material well. As many as 72.7% of participants have and will create virtual shops to promote their products and 63.6% of participants strongly agree that the ability to use social media is a must have to increase market access for MSME products.